Risco e vulnerabilidade : razões e implicações para o uso na Política Nacional de Assistência Social - Alvarenga, Mirella Souza (2012)
This study aims at analyzing how the terms "risk" and "vulnerability" were introduced in the 2004 Brazilian National Social Assistance Policy (PNAS). It will clarify the reasons and implications of using these terms in social assistance policy. Our starting point is that these terms have come along with health policy compilations. The premise is that by explaining neither the origin of these terms nor the their conceptions within the document, PNAS makers allowed different interpretations, which facilitated especially that view that is associated to the neoliberal perspective and inserted into the guidelines spread by international bodies. The study adopted oral history as method. Data were gathered from bibliographical and documental research and interviews. Content analysis approach was used. We concluded that the terms introduced in the PNAS derive from health care compilations. They were required in order to overcome care provided by segments and focalization on the poor and allow preventive interventions. However, the terms that originally aimed at overcoming every hindrance in social assistance policy ended up impeding policy operationalization just because their meaning is not clear